Karakteristik Estuari di Muara Angke pada Musim Timur - Ivonne Milichristi Radjawane; Grahadi Pandu Mughny; Gandhi Napitupulu (Jurnal Kelautan Tropis, 2024)
Estuaries are important transitional environments between freshwater and marine ecosystems. These areas are often centers of economic activity, environmental sustainability and natural resources. In this context, this study aims to investigate the estuary characteristics of Muara Angke, particularly in terms of changes in water level, salinity, and the influence of river flow in the face of changing tidal conditions. Research on estuary characteristics in one of the Ciliwung River Estuaries was conducted on August 9-10, 2015. The research area is Muara Angke, North Jakarta, DKI Jakarta Province. The measurement point consists of 11 stations starting from point A1 at the mouth of the estuary to point A11 which is the farthest station point from the estuary, with a distance of 200 m between stations. Oceanographic parameter measurements were made at 3 depths (0.2h; 0.6h and 0.8h) with 4 tidal conditions (towards the tide, tide, towards the ebb and ebb). Angke Estuary has a diurnal tidal type with a range of water levels between 0.98 m - 1.41 m and an average discharge of 7.75 m3/s during the measurement time. The results showed that the Angke Estuary has a partially mixed estuary type with salinity values at the surface increasing relatively small to the middle layer and also the bottom layer decreasing relatively small to the middle layer which indicates vertical mixing from the bottom to the surface. In addition, based on the estuary numbers (  = 0.337;  = 0.279;  = 0.593), there is a freshwater flow that is smaller or equal to the tidal influence. Salinity intrusion occurs as far as 2 km when conditions are towards high tide and  high tide.